Status Hukum Hak Atas Tanah Musnah Pasca Banjir Berdasarkan Permen ATR/BPN Nomor 3 Tahun 2024 - Tasyukur Tasyukur; Nabhani Yustisi; Joelman Subaidi; Muksalmina Muksalmina; Shira Thani (JOM, 2026)
Flood disasters frequently transform or eliminate the physical characteristics of land, generating legal uncertainty regarding the continuity of land rights. This article analyzes the legal status of land rights over land destroyed by floods under Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 3 of 2024, which amends Regulation Number 17 of 2021 concerning Procedures for Determining Destroyed Land. Employing normative juridical research with statutory and conceptual approaches, the study demonstrates that land rights are not automatically extinguished when land is affected by floods, mudflows, or temporary inundation. Rather, rights may be terminated only after the land is legally determined to be destroyed, namely when it has permanently lost its original physical characteristics, can no longer be identified, and is no longer capable of being used or utilized. The findings further reveal that the 2024 regulation strengthens legal certainty by establishing clearer criteria and administrative procedures for determining destroyed land while affirming the state's obligation to update land registration records and facilitate recovery measures, including relocation and social assistance for affected rights holders. This study contributes to the development of disaster-responsive land law by clarifying the legal distinction between temporary disaster impacts and the permanent extinction of land rights.